Detection of spontaneous hemoperitoneum in a pregnancy complicated with endometriosis during caesarean section - a case report - Chauhan, Sonali; Sharma, Jiten; Arora, Bhumika; Mittal, Shivika; Mittal, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Endometriosis is defined as the presence of endometrial glands and stroma outside the uterus. During pregnancy endometriosis and its related pain symptoms improve due to various metabolic, hormonal, immune and angiogenesis changes that occur in pregnancy. Spontaneous hemoperitoneum in pregnancy (SHiP) is a rare but serious pregnancy complication, which is associated with high rates of maternal and foetal morbidity and mortality. Endometriosis may be a potential risk factor for SHiP. Preformation of IVF on women with endometriosis may be a potential risk factor for SHiP. In gravid females with a history of endometriosis, severe abdominal pain, and a reduction of haemoglobin, physicians should always suspect SHiP because it is a life-threatening condition for both the mother and the baby. We are reporting a case of a primigravida with term gestation, taken up for emergency caesarean section in view of non-reassuring foetal heart rate. Intraoperatively there was evidence of hemoperitoneum and multiple endometriotic lesions on the posterior surface of uterus and Pouch of Douglas, Bilateral ovaries were adherent to the endometriotic growth on the posterior surface of uterus. Postoperatively, patient was stable and was discharged on postoperative day 4.